Procedure and Tools for Assessing Security at the National and Regional Levels - S. V Kazantsev (Мир новой экономики, 2018)
The Strategy of the Russian Federation national security was accepted in 2015, the Doctrine of information security of the Russian Federation - in 2016. In December 2016, Prime Minister Dmitry Medvedev instructed the Russian government to work out a Doctrine of energy security of the country. In 2017, the President Vladimir Putin proved the Strategy of economic security of the Russian Federation until 2030. We also have a Food security Doctrine of the Russian Federation, a cyber security strategy of Russia is to be developed too, etc. Naturally, the question arises about the method that may be used for estimation the levels of different types of security - national, economic, demographic, food, ecological, cyber, energy, transport security, etc. A structure of the methodology and method of security assessment are considered in this paper. The later were tested in practical calculations. The author concludes, that all considered approaches can be used for estimation the levels of economic security of the country and the subjects of the Russian Federation. Their comparison allowed to identify the main stages of the assessment. They are: determination of a set of initial indicators, their quantification, normalization, calculation of the generalizing indicators for groups of normalized indicators, the subjects of the Russian Federation, and the country as a whole.